(untitled) (Research, Society and Development, 2024)
Objective: To analyze the perception of hospitalized pregnant women about the importance of obstetric physiotherapy in a reference public maternity hospital, as well as to identify the contribution of physiotherapy to the evolution of pregnant women during the hospitalization process. Methods: This is an observational, cross-sectional, and descriptive study, with a quantitative approach, carried out with 31 high-risk pregnant women over 18 years of age, hospitalized in a highly complex public reference maternity hospital. For data collection, a questionnaire on socio-personal characterization and obstetric physiotherapy was used, containing 26 easy-to-solve questions. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 21.0. The significance level adopted was p-value <0.05. The comparison between sociodemographic characteristics according to knowledge about physiotherapy was performed using Fisher’s exact test. Results: the obstetric variable "Gestational age" showed a significant correlation (p= 0.011) between prior knowledge of obstetric physiotherapy. The majority (58.1%) noticed differences in pregnancy with and without physiotherapeutic assistance. Conclusion: it was concluded that the level of knowledge and perception of the participants were considered satisfactory about physiotherapy practices in high-risk pregnant women referred to the maternity ward who received physiotherapy services. Furthermore, it was shown that women’s knowledge from other studies about the role of physiotherapy in obstetrics is still limited.